2015
DOI: 10.1007/s10457-015-9855-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the integrated livestock–forest system on recovery of trichostrongylid nematode infective larvae from sheep

Abstract: Your article is protected by copyright and all rights are held exclusively by Springer Science +Business Media Dordrecht. This e-offprint is for personal use only and shall not be selfarchived in electronic repositories. If you wish to self-archive your article, please use the accepted manuscript version for posting on your own website. You may further deposit the accepted manuscript version in any repository, provided it is only made publicly available 12 months after official publication or later and provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 16 publications
0
9
0
2
Order By: Relevance
“…At Rio Grande do Sul, Echevarria et al (1993) reported a similar efficiency of the ICL system in the decontamination of pastures by GIN larvae. The same was not observed by other researchers that evaluated the integrated livestock-forest systems (ILF) (Faria et al, 2016;Oliveira et al, 2017a). Faria et al (2016), when evaluating the pasture contamination in the ILF system, found a higher number of GIN infective larvae of sheep in the ILF system compared to the conventional system.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…At Rio Grande do Sul, Echevarria et al (1993) reported a similar efficiency of the ICL system in the decontamination of pastures by GIN larvae. The same was not observed by other researchers that evaluated the integrated livestock-forest systems (ILF) (Faria et al, 2016;Oliveira et al, 2017a). Faria et al (2016), when evaluating the pasture contamination in the ILF system, found a higher number of GIN infective larvae of sheep in the ILF system compared to the conventional system.…”
Section: Discussionmentioning
confidence: 49%
“…The same was not observed by other researchers that evaluated the integrated livestock-forest systems (ILF) (Faria et al, 2016;Oliveira et al, 2017a). Faria et al (2016), when evaluating the pasture contamination in the ILF system, found a higher number of GIN infective larvae of sheep in the ILF system compared to the conventional system. Certainly, there are differences between the ICL and ILF regarding the contamination of pastures by GIN L3.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Almeida et al (2018) avaliaram quatro tipos de integração lavoura pecuária quanto ao nível de contaminação da pastagem por larvas infectantes (L3), e verificaram que o período de 300 dias sem a presença de animais em área de pastejo demonstrou ser eficiente para a descontaminação por larvas infectantes de nematódeos gastrintestinais de ovinos. Contudo, Faria et al (2016) reforçam que a estratégia de aplicação dos sistemas com IPF, por exemplo, pode ser aplicado de diferentes maneiras, o que está associado às condições climáticas de cada região, a qual pode mudar significativamente e no nível de infestação da pastagem. Dessa forma, de acordo com esses autores, faz-se necessário avaliar as estratégias de manejo de controle de nematoides para se ter uma melhor eficiência.…”
Section: Issn: 2525-8761unclassified
“…Em um trabalho realizado por Faria et al (2016) Diante desses achados, mais estudos precisam ser conduzidos para encontrar a melhor combinação de manejo dentro do sistema para controle de verminose dos ovinos, principalmente na fase de terminação de cordeiro, principal produto da ovinocultura de corte.…”
Section: Issn: 2525-8761unclassified